How We Think about Temporal Words: A Gestural Priming Study in English and Chinese - Ng, Melvin M. R.; Goh, Winston D.; Yap, Melvin J.; Tse, Chi-Shing; So, Wing-Chee (Frontiers in Psychology, 2017)
Spatial metaphors are used to represent and reason about time. Such metaphors are typically arranged along the sagittal axis in most languages. For example, in English, “The future lies ahead of us” and “We look back on our past.” This is less straightforward for Chinese. Specifically, both the past and future can either be behind or ahead. The present study aims to explore these cross-linguistic differences by priming auditory targets (e.g., yesterday) with either a congruent (i.e., pointing forwards) or incongruent (i.e., pointing backwards) gesture. Two groups of college-age young adult participants (English and Chinese speakers) made temporal classifications of words after watching a gestural prime. If speakers represent time along the sagittal axis, they should respond faster if the auditory target is preceded with a gesture indicating a congruent vs. incongruent spatial location. Results showed that English speakers responded faster to congruent gesture-word pairs than to incongruent pairs, mirroring spatio-temporal metaphors commonly recruited to talk about time in their native language. However, such an effect of congruency was not found for Chinese speakers. These findings suggest that while the spatio-temporal metaphors commonly recruited to talk about time help to structure the mental timelines of English speakers, the varying instances in how time is represented along the sagittal axis in Chinese may lead to a more variable mental timeline as well. In addition, our findings demonstrate that gestures may not only be a means of accessing concrete concepts in the mind, as shown in previous studies, but may be used to access abstract ones as well.